(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The article discusses the importance of developing the creative abilities of preschool children and the use of ART pedagogical tools in visual arts classes, analysis of literature on the topic, increasing the creative abilities of children in drawing classes, interest in children’s fine arts, as well as the formation of their aesthetic taste and sophistication. Based on state requirements for the development of children of primary and preschool age, an improvement is recommended, a model for the development of the creative abilities of children in the preparatory group with the help of art pedagogy.